Wave attenuation in partially saturated porous rocks - New observations and interpretations across scales - Caspari, Eva (2014)
Seismic waves propagating in porous rocks saturated with two immiscible fluids can be strongly attenuated. Predicting saturation effects on seismic responses requires a sound understanding of attenuation and velocity dependencies on the fluid distribution. Decoding these effects involves interpreting laboratory experiments, analyzing well-log data, and performing numerical simulations. Despite striking differences among scales, flow regimes, and frequency bands, some aspects of wave attenuation can be explained with a single mechanism ? wave-induced pressure diffusion. Different facets of wave-induced pressure diffusion can be revealed across scales.